Influence of cultivar and plant density on the growth, bulb yield and quality traits of onion (Allium cepa L.) - Yebirzaf Yeshiwas; Melkamu Alemayehu; Enyew Adgo (Scientific Reports)
Abstract Onion is the most important and widely cultivated cash-generating crop in Ethiopia. Onion production is limited by several factors, and its production and productivity are low. Among the many contributing factors, a lack of improved cultivars and improper plant density are the major limiting factors. This study addressed the critical challenges of onion cultivation in Ethiopia, with a focus on the impact of planting density and onion cultivar. Three hybrid onion cultivars and one open-pollinated onion cultivar were evaluated at three testing sites (Koga, Woramit and Woreta) under irrigated conditions in 2021/2022 via a randomized complete block design with three replications. The results of the present study revealed that the growth and yield of onion plants were influenced by the main effects of plant density and onion cultivar across locations. The Russet and Jambar hybrid cultivar, which had a relatively high plant density, exhibited superior performance across all locations. They consistently presented the highest values for bulb diameter, average bulb weight, harvest index, firmness, total bulb yield and marketable bulb yield across all locations. The marketable bulb yield was positively correlated with the bulb weight and bulb diameter of the onion. The Russet (28.09 t ha− 1) and Jambar (26.61 t ha− 1) cultivars presented the highest marketable bulb yields and were generally superior in terms of most of the growth, yield and quality parameters. The highest marketable bulb yield (28.42 t ha− 1) was recorded for the onion cultivars in the higher plant population (666,666 plants ha− 1), in which the spacing was 5 cm × 20 cm × 40 cm between plants, rows and double rows. Accordingly, the use of hybrid onion cultivars (Russet and Jambar) along with higher plant populations (5 cm between plants × 20 cm between rows × 40 cm between double rows) enhances the productivity of onion in the study area and areas with similar agroecology. Since this study was the first of its kind in the study area, it is advisable to consider other hybrid onion cultivars with relatively high plant densities.